2020
DOI: 10.1109/tci.2019.2948729
|View full text |Cite
|
Sign up to set email alerts
|

Coding Mask Design for Single Sensor Ultrasound Imaging

Abstract: We study the design of a coding mask for pulse-echo ultrasound imaging. We are interested in the scenario of a single receiving transducer with an aberrating layer, or 'mask', in front of the transducer's receive surface, with a separate co-located transmit transducer. The mask encodes spatial measurements into a single output signal, containing more information about a reflector's position than a transducer without a mask. The amount of information in such measurements is dependent on the mask geometry, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this paper, only one randomly generated coding pattern was adopted, which might still be optimized towards our application scenario. Our previous work [6] has shown that this may improve results further. Furthermore, we are aiming to apply our device for flow/function monitoring in the carotid artery, for which the requirements of spatial separability might be more lenient than for B-mode imaging.…”
Section: Discussionmentioning
confidence: 87%
“…In this paper, only one randomly generated coding pattern was adopted, which might still be optimized towards our application scenario. Our previous work [6] has shown that this may improve results further. Furthermore, we are aiming to apply our device for flow/function monitoring in the carotid artery, for which the requirements of spatial separability might be more lenient than for B-mode imaging.…”
Section: Discussionmentioning
confidence: 87%
“…Using the matched filter A, we can obtain the system in (2), Z = A H X = A H AS + N = HS + N, with H = A H A, which is not a shift-invariant matrix. Here, A is constructed using the k-wave toolbox in MATLAB for an imaging system with 128 transmitters and receivers [26] [27]. Furthermore, the A matrix is constructed in the frequency domain instead of the time domain.…”
Section: B Results With Sensing Matrix Obtained From K-wavementioning
confidence: 99%